PENGARUH SOLID PADA SAKURA BLOK TERHADAP KECERNAAN SERAT KASAR SAPI LOKAL KAUR YANG DIBERI RANSUM BASAL RUMPUT LAPANGAN: Effect of Solid Sakura Block on Crude Fiber Digestibility of Local Kaur Cattle Given Basal Field Grass Ration - Jarmuji; Badarina, Irma; Herdiansah, Riko (Wahana Peternakan, 2024)
This study aims to evaluate the effect of sakura block supplementation using solid as a substitute for bran on crude fiber digestibility of local Kaur beef cattle fed natural grass.The research design used was the Latin Square Design (LSD) with treatments consisting of P1(16.5% bran + 5.5% solid), P2(11% bran+ 11% solid), P3(5.5% bran + 16 .5% Solid), P4(22% Solid). This research used 4 beef cattle, each period consisting of 15 days of treatment, where the last 5 days of each period were used to collect crude fiber digestibility. The results of the study showed that sakura block supplementation using solid as a substitute for bran had no significant effect (P>0.05) on natural grasses crude fiber intake, sakura block crude fiber intake, fecal crude fiber production, and crude fiber digestibility. . It was concluded that sakura block supplementation using solid did not reduce crude fiber intake, crude fiber content in feces and crude fiber digestibility in local kaur cattle fed basalt field grass rations. Keywords: Local Kaur Beef Cattle, Sakura Block, Palm Sludge, Digestibility, Crude Fiber.